Sumbangan Peradapan Mesir Kuno Bagi Kehidupan Di Dunia - Setiawati, Debi; Ramadani, Nur Kharisma; Faraniza, Dhea (CV. ITTC INDONESIA, 2022)
Ancient Egypt is a civilization in the northeastern part of Africa. These civilizations were concentrated along the middle to the lower reaches of the Nile which reached its heyday around the 2nd century BC. During what is known as the new kingdom period. Its area spans the Nile Delta region in the North, to Jebel Barkal in the fourth Cataract of the Nile. At certain times, ancient Egyptian civilization extended to the southern Levant, the Eastern Desert, the Red Sea coast, the Sinai peninsula, and the western desert (concentrating on several oases). Egypt is a country that has a long history in the past. Its civilization is recognized by the world as one of the most advanced civilizations that has ever existed. The pyramids, the stories of Pharaoh, Cleopatra, and the spinx are symbols of how much history has happened in this land that the Nile flows through. As a country rich in history, Egypt has provided many great discoveries that have been of use until now. It's no wonder that many world researchers are interested in exploring the history of Ancient Egypt, historical discoveries from the Ancient Egyptians whose benefits are widely felt today.